2013
DOI: 10.1101/gad.221515.113
|View full text |Cite
|
Sign up to set email alerts
|

DmGTSF1 is necessary for Piwi–piRISC-mediated transcriptional transposon silencing in the Drosophila ovary

Abstract: The Piwi-piRNA (PIWI-interacting RNA) complex (PiwipiRISC) in Drosophila ovarian somatic cells represses transposons transcriptionally to maintain genome integrity; however, the underlying mechanisms remain obscure. Here, we reveal that DmGTSF1, a Drosophila homolog of gametocyte-specific factor 1 (GTSF1) (which is required for transposon silencing in mouse testes), is necessary for Piwi-piRISC to repress target transposons and neighboring genes. DmGTSF1 depletion affected neither piRNA biogenesis nor nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
181
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(199 citation statements)
references
References 39 publications
13
181
1
4
Order By: Relevance
“…6A,C; Supplemental Fig. S5D; Ohtani et al 2013). Consistent with this, HP1a is present at piRNA-targeted TE insertions as well as at the flanking genomic regions in a Piwi-dependent manner (Fig.…”
Section: Cg9754/silencio Is Required For H3k9 Methylation and Transcrsupporting
confidence: 66%
See 1 more Smart Citation
“…6A,C; Supplemental Fig. S5D; Ohtani et al 2013). Consistent with this, HP1a is present at piRNA-targeted TE insertions as well as at the flanking genomic regions in a Piwi-dependent manner (Fig.…”
Section: Cg9754/silencio Is Required For H3k9 Methylation and Transcrsupporting
confidence: 66%
“…However, neither of these factors is conserved in animals. In turn, two proteins with largely unknown functions that are required for piRNA-guided transcriptional silencing in animals (Gtsf1/Asterix and Maelstrom) (Sienski et al 2012;Donertas et al 2013;Muerdter et al 2013;Ohtani et al 2013) are absent in S. pombe, highlighting significant molecular differences in these two systems. Moreover, the Piwi-piRNA complex fails to mediate transcriptional silencing if recruited artificially (not involving a piRNAtarget interaction) to a reporter RNA in a Drosophila cell culture model that expresses a fully functional piRNA pathway centered on nuclear Piwi (Post et al 2014).…”
mentioning
confidence: 99%
“…Several recent genome-wide studies examining mutants and genetic perturbations of the Piwi pathway in flies have confirmed the transcriptional silencing mechanism of TEs by PIWI via a transcription-repressive chromatin state (Sienski et al 2012;Huang et al 2013;Le Thomas et al 2013;Ohtani et al 2013;Rozhkov et al 2013). Here, we present a reporter assay platform that shows a dependence on PIWI and piRNA complementarity for triggering robust gene silencing, and the silencing capacity appeared to be present in both TE-directed piRNAs as well as genic piRNAs.…”
Section: Discussionmentioning
confidence: 95%
“…Although miRNAs and endo-siRNAs are expressed in both animals and plants, piRNA expression is largely restricted to animal gonads, where they primarily mediate TE silencing for genome integrity and germ cell development (Thomson and Lin 2009;Siomi et al 2011). piRNAs act as guides for the cleavage of TE transcripts by PIWI protein Slicer activity in the cytoplasm, which often couples with the ping-pong cycle, or for Slicer-independent heterochromatin formation at TE loci in the nucleus (Sienski et al 2012;Dönertas et al 2013;Huang et al 2013;Le Thomas et al 2013;Muerdter et al 2013;Ohtani et al 2013).…”
Section: Introductionmentioning
confidence: 99%